PENGARUH KETERLIBATAN INFLUENCER DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN BRAND SKINCARE SKINTIFIC - Allisa Isnaini; Dian Sudianti, Jelita Rismawati, Nadya Shevyani, Sarah Ayu Putri S, Destia Rika Purnamawati (Jurnal Ekonomi dan Bisnis, 2024)
This research uses a qualitative research method approach. Which is to find out the results of the influence of influencer involvement and social media marketing on purchasing decisions for the Skintific skincare brand. Technology is becoming an increasingly important part of everyone's life because of its rapid development, therefore social media is very influential for brand promotion media, plus the collaboration of influencers with social media has a big influence on increasing consumer purchasing decisions.